(untitled) (Journal of actual problems of jurisprudence, 2018)
Private life is a multifaceted concept, which includes a whole range of different components for the concept of its essence is necessary to apply to a variety of opinions on its nature and essence, which exist not only in jurisprudence, but also in sociology, philosophy, ethics and other areas knowledge. Revealing all aspects of manifestations of private life – is a fundamental challenge for the legal science. Because it may be important to the current legislation in order to improve the existing and develop new legal tools to protect it. We offer, in view of the existing diversity of opinion, the right to privacy can be defined as a legal capacious category, consisting of a number of competences. Key words: privacy, private life, the right to privacy, integrity, privacy restrictions.